The Ibalon. [anthology].
It is not sure whether or not the story is authentic or not. Nevertheless, it has been embraced by the Bicol people. Handiong brought order and civilization to the wild area, but he also destroyed the land and all of the creatures that lived there. Forests disappeared as new settlements grew. The story shows the cautionary tale of man ignoring nature and forgetting to find a balance between conquest and living peacefully in harmony with nature. - from https://www.reference.com/art-literature/summary-ibalon-2c5d174a1b8c4eb0
Found in: Philippine Folk Literature : The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.